Rancang Bangun Pendeteksi Penyakit Jantung menggunakan Teknik Algoritma Fuzzy Logic berbasis IoT - Irma Salamah; Syafa Naura Afifa; Emilia Hesti (Jurnal Pendidikan Informatika (EDUMATIC), 2022)
Heart rate is a health indicator that has the advantage of assessing or knowing a person's health quickly. It is useful as the first diagnosis of the presence or absence of heart disorders. By building an IoT (Internet of Things) based heart rate monitoring system, it is hoped that it can be monitored, and through Android can check the heart rate. An IoT system is an idea that can expand and utilize a relationship that is connected continuously. Where IoT can monitor a person's condition so that a person's condition remains monitored 24 hours. This study aims to design a heart disease detector using an iot-based fuzzy logic algorithm technique. The method used to design this tool is the waterfall method. In the design of an IoT-based heart rate tool, it can directly find out the heart rate experienced by high, low, or normal and automatically there are already recommendations for exercise and food according to the heart rate. Testing this tool uses hardware consisting of a max30100 sensor, nodeMCU, and an android application as an interface. The results of this study show that the tool created has an error percentage between 0.1% to 6.2%, and all data from the heart rate tool results are directly sent to the Android application in real-time based on the available Internet network connection.